Quantification of continuous evolution of full-field stress associated with shear deformation of faults using three-dimensional printing and phase-shifting methods. (February 2020) - Ju, Yang; Wan, Changbing; Ren, Zhangyu; Mao, Lingtao; Fu, Guoming; Chiang, Fu-pen
Abstract: Fault deformation or slip activated by underground mining, hydraulic fracture stimulation, and construction activities can cause devastating earthquakes or rockbursts. Fault deformability is significantly affected by the distribution and evolution of non-uniform stress around the faults. However, quantifying the continuous evolution of the full-field stress near natural rough faults using conventional methods is a challenging task due to the difficulties in discriminating and extracting stresses near a rough fault. This study proposes an optical characterization method to extract and quantify the continuous distributions and evolutions of the full-field principal stress difference and shear stress around a rough fault model. Three-dimensional (3D) printing technology and stress-sensitive photopolymers were utilized to fabricate a transparent rough fault model according to Barton's standard rough profiles. A planar testing device was designed to mimic geostress conditions and fault deformation. The conventional phase-shifting method and unwrapping algorithm were modified to quantify the continuous evolution of the principal stress difference and shear stress near rough faults. The effect of fault roughness on the distribution and evolution of the full-field stresses around the fault was also evaluated. A positive relationship between the undulating angle and the near-fault stress was established for the rough fault model. Results show that the proposed method works well for quantifying and visualizing full-field stress distribution and evolution during fault deformation.